2017
DOI: 10.5194/bg-14-2407-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean acidification on Arctic phytoplankton blooms and dimethyl sulfide concentration under simulated ice-free and under-ice conditions

Abstract: Abstract. In an experimental assessment of the potential impact of Arctic Ocean acidification on seasonal phytoplankton blooms and associated dimethyl sulfide (DMS) dynamics, we incubated water from Baffin Bay under conditions representing an acidified Arctic Ocean. Using two light regimes simulating under-ice or subsurface chlorophyll maxima (low light; low PAR and no UVB) and ice-free (high light; high PAR + UVA + UVB) conditions, water collected at 38 m was exposed over 9 days to 6 levels of decreasing pH f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 106 publications
4
34
2
Order By: Relevance
“…In line with our results, Hussherr et al (2017) found C. socialis/gelidus to dominate their experimental assemblages over the full range of the pH treatments (8.1-7.2; achieved by acid and bicarbonate addition) from an experiment initiated at the same location. Our results also agree well with previous laboratory experiments, which have shown that Antarctic Chaetoceros isolates show little to no stimulation by increasing pCO 2 levels (Boelen et al 2011;Trimborn et al 2013;Hoppe et al 2015).…”
Section: Assemblages Did Not Respond To Ocean Acidificationsupporting
confidence: 90%
See 3 more Smart Citations
“…In line with our results, Hussherr et al (2017) found C. socialis/gelidus to dominate their experimental assemblages over the full range of the pH treatments (8.1-7.2; achieved by acid and bicarbonate addition) from an experiment initiated at the same location. Our results also agree well with previous laboratory experiments, which have shown that Antarctic Chaetoceros isolates show little to no stimulation by increasing pCO 2 levels (Boelen et al 2011;Trimborn et al 2013;Hoppe et al 2015).…”
Section: Assemblages Did Not Respond To Ocean Acidificationsupporting
confidence: 90%
“…C. socialis/gelidus was also dominating the [5 lm fraction of the initial and final assemblages of another experiment initiated with waters from within the DCM at the same time as our experiment (Hussherr et al 2017). As C. socialis/ gelidus has been shown to be the most abundant diatom species in the DCM throughout Canadian Arctic waters (Martin et al 2010) and to commonly form blooms in Baffin Bay in summer (Booth et al 2002), we conclude that its dominance can be held representative for in situ dynamics and that it is not an artifact from our experimental set-up.…”
Section: Assemblages Did Not Respond To Ocean Acidificationsupporting
confidence: 57%
See 2 more Smart Citations
“…Svalbard (Archer et al 2013;Riebesell et al 2013) and one shipboard microcosm experiment with seawater collected from Baffin Bay (Hussherr et al 2017). Both studies reported significant reductions in DMS concentrations with increasing levels of pCO 2 during seasonal phytoplankton blooms.…”
mentioning
confidence: 99%